Effect of Resin Cement Color on the Final Color of Lithium Disilicate All-Ceramic Restorations - Fariborz Vafaee; Bijan Heidari; Masoumeh Khoshhal; Amirarsalan Hooshyarfard; Mahmoud Izadi; Armaghan Shahbazi; Abbas Moghimbeigi (Tehran University of Medical Sciences, 2018)
Objectives: Obtaining an adequate ceramic thickness to mask the substructure color is not always feasible, and appropriate use of a cement may be the only solution. This study aimed to evaluate the effect of the color of Variolink II resin cement on the final color of lithium disilicate glass ceramic restorations. Materials and Methods: In this in-vitro study, 90 discs of IPS e.max Press ceramic were evaluated. The ceramic discs were cemented to composite and amalgam blocks. The effect of the cement color and substructure on the final color of ceramic was analyzed by calculating the color change (∆E) value using a spectrophotometer. Data were analyzed via three-way analysis of variance (ANOVA) and Tukey's test. Results: The cement color had a statistically significant effect on the final color of ceramic (P≤0.001). The white, yellow, and translucent cements caused the highest color change (ΔE=4.558, 3.308, and 2.649, respectively). The effect of composite substructure and the yellow cement on the final color was less prominent compared to other combinations of cement and substructure (ΔE=2.043). The white cement over amalgam substructure showed the greatest effect on the final color (ΔE=4.890). The ΔE in HO group was less than that of other combinations (P<0.05), and the greatest ΔE was reported in MO group with the white cement (∆E=6.255). Conclusions: The final color of the restoration is influenced by the cement color. Therefore, when IPS e.max Press is used over a metal core, it is recommended to use a cement with an HO ceramic.